2022
DOI: 10.3389/fbioe.2022.826093
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Hepatic Plate-Like Liver Model for Statin-Induced Hepatotoxicity Evaluation

Abstract: Background: Drug-induced liver injury is one of the main reasons of withdrawals of drugs in postmarketing stages. However, an experimental model(s) which can accurately recapitulates liver functions and reflects the level of drug hepatotoxicity is lack. In this study, we assessed drug hepatotoxicity using a novel three-dimensional hepatic plate-like hydrogel fiber (3D-P) co-culture system.Methods: During the 28-days culture period, the liver-specific functions, hepatocyte polarity, sensitivity of drug-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Therefore, when culturing hepatocytes in vitro, restoring and maintaining their polarity is crucial for enhancing their functional activity. Increasing evidence suggests that the establishment and maintenance of hepatocyte polarity are closely related to intercellular interactions and the interaction between cells and the extracellular matrix [55]. Based on HepRG cells exhibiting higher albumin secretion, CYP3A4 expression, and ammonia metabolism on the PET-dECM scaffold, this section examines the mRNA expression of polarity genes, stemness genes, and genes related to the aforementioned hepatocyte functions in HepRG cells cultured on different scaffolds on the sixth day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when culturing hepatocytes in vitro, restoring and maintaining their polarity is crucial for enhancing their functional activity. Increasing evidence suggests that the establishment and maintenance of hepatocyte polarity are closely related to intercellular interactions and the interaction between cells and the extracellular matrix [55]. Based on HepRG cells exhibiting higher albumin secretion, CYP3A4 expression, and ammonia metabolism on the PET-dECM scaffold, this section examines the mRNA expression of polarity genes, stemness genes, and genes related to the aforementioned hepatocyte functions in HepRG cells cultured on different scaffolds on the sixth day.…”
Section: Discussionmentioning
confidence: 99%
“…However, simple 3D culture techniques, such as ULAPs and HDs, are unable to simulate cell-ECM interactions, which are important in supporting cell proliferation and differentiation [24]. Superior 3D culture techniques, such as hydrogels and scaffolds, need complex handling [25]. Therefore, a simple method for 3D hepatocyte modeling with an ECM microenvironment that can be used for HTS screening is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Liver dysfunction may arise in many hepatic diseases and can also be caused by various factors such as viruses, alcohol use, and drug-induced liver injury (DILI). Among these factors, DILI is a major cause of acute liver failure (ALF) and one of the leading indications for liver transplantation ( Chalasani et al, 2015 ; Xu et al, 2022 ). It's reported that the annual incidence of DILI in the general population ranges between 13 and 24 cases per 100,000 inhabitants ( Sgro et al, 2002 ; Bjornsson et al, 2013 ; Shen et al, 2019 ; Kamath et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%